2016
DOI: 10.1186/s41182-016-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tuberculosis and associated risk factors in the Central Prison of Mbuji-Mayi, Democratic Republic of Congo

Abstract: BackgroundTuberculosis still remains a major public health concern in several provinces of the Democratic Republic of Congo, especially in prison settings. The present study aimed at determining tuberculosis (TB) prevalence and associated risk factors in inmates of the Mbuji-Mayi Central Prison.MethodsThis cross-sectional study was performed over a 6-month period (January to June 2015) in Mbuji-Mayi Central Prison. A total of 733 inmates were screened systematically for TB. The diagnosis was based on clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
0
18
4
3
Order By: Relevance
“…The pooled prevalence result, on the other hand, was less than prevalence reports from Zambian prisons (22.7%) [ 25 ] and Democratic Republic of Congo (17.7%) [ 26 ]. This might be due to the laboratory tests used to diagnose TB.…”
Section: Discussioncontrasting
confidence: 62%
“…The pooled prevalence result, on the other hand, was less than prevalence reports from Zambian prisons (22.7%) [ 25 ] and Democratic Republic of Congo (17.7%) [ 26 ]. This might be due to the laboratory tests used to diagnose TB.…”
Section: Discussioncontrasting
confidence: 62%
“…Species identification and drug susceptibility testing performed with Genotype MTBDRplus Active TB Henostroza et al, 2013 [ 46 ] Zambia Cross-sectional study Lusaka Central Prison 2011 Digital X-ray/sputum smear microscopy, LED fluorescence, Lowenstein-Jensen Medium) culture. Active TB Kalonji et al, 2016 [ 47 ] Democratic Republic of the Congo Cross-sectional study Mbuji-Mayi Central Prison 2015 Clinical examination and bacteriological tests Active TB Karamagi et al, 2018 [ 48 ] Uganda Cross-sectional study 16 central and farm prisons (Names not specified) 2017 Combined quality improvement with facility-led active case finding (QI-ACF) Active TB Kayomo et al, 2018 [ 49 ] Democratic Republic of the Congo Cross-sectional study Mbuji-Mayi Central Prison 2015 Xpert MTB/RIF assay Active TB Kwabla et al, 2015 [ 50 ] Ghana Cross-sectional study Ho Prison 2014 Sputum smear microscopy Active TB Maggard et al, 2015 [ 51 ] Zambia Cross-sectional study Lusaka Central Prison, Livingstone Central Prison, Kabwe Prison Complex, 2011 Fluorescence microscopy, cultures, X-rays and physical examinations. Active TB Merid et al, 2018 [ 52 ] Ethiopia Cross-sectional study Hawassa prison 2016 Acid-fast bacilli, smear microscopy and molecular diagnostic testing (Xpert® MTB/RIF) Active TB Noeske et al, 2006 [ 53 ] Cameroon Cross-sectional study New Bell Central Prison of Douala 2004 Smear microscopy and/or culture Active TB Owokuhaisa et al, 2014 [ …”
Section: Resultsmentioning
confidence: 99%
“…All 31 articles scored between 57 and 86%. The majority (45.2%) of the included articles scored 71.4% (14/31) [ 36 , 39 , 40 , 42 , 45 , 46 , 49 , 50 , 53 56 , 60 , 61 ] and 10 (32.2%) scored 57.1% [ 35 , 37 , 38 , 41 , 43 , 44 , 47 , 48 , 52 , 57 ]. The remaining seven included articles scored the highest (85.7%) [ 32 34 , 51 , 58 , 59 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of structural and host determinants have been implicated in the high rates of TB infection and disease observed in prisons 11 . These include factors associated with increased transmissibility of the disease, such as overcrowding and ventilation 11 , as well host factors associated with both TB risk and incarceration, such as nutritional deficiency 12 , HIV infection, smoking 13 , 14 and drug use 15 , 16 . Previous studies have identified low vitamin D levels among prisoners in correctional facilities, likely due to prolonged indoor incarceration with insufficient sunlight exposure or dietary sources of vitamin D 7 .…”
Section: Introductionmentioning
confidence: 99%